Cloud Computing in Smart Cities: Privacy, Ethical and Social Issues - Alkhazali A.R.M.; Khasawneh A.M.; Alzoubi S.; Magableh M.; Mohamed R.R.; Pandey B. (Institute of Electrical and Electronics Engineers Inc., 2024)
The rapid development of cloud computing technologies has revolutionized various sectors, and smart cities are no exception. Smart cities leverage cloud computing to optimize urban services, enhance resource management, and improve the overall quality of life for their inhabitants. However, as these technological advancements proliferate, concerns about privacy, ethical considerations, and social implications have emerged. This research paper critically examines the multifaceted challenges associated with the integration of cloud computing in smart cities, shedding light on the potential risks and highlighting the need for comprehensive solutions. The research employs a mixed-methods approach, combining quantitative data analysis and qualitative case studies to offer a comprehensive perspective on the identified issues. The primary focus lies in identifying privacy risks, ethical dilemmas, and social disparities that arise due to the extensive use of cloud-based systems and data in smart cities. Furthermore, the study investigates the role of key stakeholders, including governments, technology providers, and citizens, in mitigating or exacerbating these challenges. Key findings reveal that while cloud computing empowers smart cities with unparalleled capabilities, it also exposes residents' personal information to potential breaches and misuse. Ethical concerns arise from the handling of sensitive data, data ownership, and algorithmic biases that could perpetuate discrimination. Moreover, social issues like the digital divide and access disparities may further exacerbate existing inequalities in smart city implementation. This research paper concludes by proposing a comprehensive framework of guidelines and best practices to address the identified issues effectively. These recommendations encompass enhanced data privacy measures, transparent and accountable data governance, the promotion of ethical data usage, and inclusive strategies to bridge social disparities. By adopting these measures, smart cities can harness the full potential of cloud computing while safeguarding individual rights and fostering a more equitable and inclusive urban environment. Overall, this study underscores the critical importance of addressing privacy, ethical, and social challenges in the context of cloud computing in smart cities. By adopting a holistic and proactive approach, city planners, policymakers, and technology providers can build sustainable and responsible smart cities that ensure the well-being and dignity of their residents in the digital era. 2023 IEEE.